2007
DOI: 10.1038/sj.onc.1210299
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of c-Myc in primary effusion lymphoma by Kaposi's sarcoma herpesvirus latency-associated nuclear antigen

Abstract: Primary effusion lymphoma (PEL) is a rare subtype of non-Hodgkin's lymphoma, which is associated with infection by Kaposi's sarcoma herpesvirus (KSHV)/human herpesvirus-8. The c-Myc transcription factor plays an important role in cellular proliferation, differentiation and apoptosis. Lymphomas frequently have deregulated c-Myc expression owing to chromosomal translocations, amplifications or abnormal stabilization. However, no structural abnormalities were found in the c-myc oncogene in PEL. Given that c-Myc i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 48 publications
0
89
0
Order By: Relevance
“…Additional experiments are needed to determine whether the association of vIRF-3 with c-Myc can also alter the DNA-binding specificity of c-Myc, which may result in the activation of a distinct set of genes that are not regulated by c-Myc alone. Recently, two groups linked another KSHV-encoded latent gene, LANA, to impaired c-Myc degradation in PEL cells (59,60). They showed that LANA stabilizes c-Myc protein by preventing its phosphorylation on threonine 58 and simultaneously stimulates its phosphorylation at serine 62, which leads to c-Myc transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments are needed to determine whether the association of vIRF-3 with c-Myc can also alter the DNA-binding specificity of c-Myc, which may result in the activation of a distinct set of genes that are not regulated by c-Myc alone. Recently, two groups linked another KSHV-encoded latent gene, LANA, to impaired c-Myc degradation in PEL cells (59,60). They showed that LANA stabilizes c-Myc protein by preventing its phosphorylation on threonine 58 and simultaneously stimulates its phosphorylation at serine 62, which leads to c-Myc transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%
“…All of them are linked to viral maintenance and to the perturbation of the host immune response (Dourmishev et al, 2003;zur Hausen, 2006;Areste´and Blackbourn, 2009). In particular, several of these proteins (LANA, v-cyclinD, vFLIP and kaposin) can affect the main tumorigenic pathways involved in regulating important tumor suppressors and oncogenic genes in mammals (Godden-Kent et al, 1997;Friborg et al, 1999;Radkov et al, 2000;Fujimuro et al, 2003;Guasparri et al, 2004;McCormick and Ganem, 2005;Bubman et al, 2007;Di Bartolo et al, 2008).…”
Section: Viral Epigenomes In Human Tumorigenesis Af Fernandez and M Ementioning
confidence: 99%
“…Unlike other lymphomas, no signature translocation or single gene mutation has been associated with PEL to date. The p53 tumor suppressor protein appears functional in PEL cell lines, 15 the Myc locus un-rearranged, although the protein is unusually stable, 16 and no amplifications or deletions are reported for Bcl-2, 2 Bcl-6, 17 Ras, 2 the catalytic subunit of PI3K, 18 phosphatase with tensin homolog or p16/INK4. 18 We therefore used the Affymetrix 6.0 single nucleotide polymorphism (SNP)-based microarray to conduct comparative genomic hybridization (CGH) to look at the global genomic profile of PEL cells.…”
Section: Introductionmentioning
confidence: 99%